The Local News Sources in The Kurdish Electronic Press: Analytical Study of Local News Sources At The Xendan Website From 1-31/3/2016 - Abdulkhaliq Ibrahim Mstaffa; Jawad Mohammadameen Issa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study aims to identify local news sources in the Kurdish electronic media, the study is a descriptive study using the survey method and rely on the content analysis mannar to collect the necessary information about local news sources. The study community consists of all Kurdish electronic news sites, and the Xendan site was chosen as a sample of the study, and one of the most important findings of the study is that the Xendan website relied heavily on its own resources including representatives and correspondents in collecting and disseminating local news.